Antihypertensive and antioxidant effects of supplementation with red wine pomace in spontaneously hypertensive rats. Issue 7 (12th June 2017) - Del Pino-García, Raquel; Rivero-Pérez, María D.; González-SanJosé, María L.; Croft, Kevin D.; Muñiz, Pilar
Abstract : 4-Week supplementation with a new red wine pomace seasoning (RWPS) decreased blood pressure, ameliorated vascular oxidative stress, and improved NO bioavailability in Spontaneously Hypertensive Rats (SHR). Abstract : Hypertension is associated with enhanced vascular oxidative stress and impaired endothelial function, which is related to an imbalance between reactive oxygen species and nitric oxide bioavailability. Short-term supplementation with a polyphenol-rich powdered red wine pomace seasoning (RWPS) was investigated for its effects on blood pressure and biomarkers of endothelial dysfunction and oxidative status in a model of essential hypertension. Male spontaneously hypertensive rats (SHRs) and normotensive Wistar-Kyoto rats (12-week-old, 5 rats per group) were administered RWPS (300 mg kg −1 day −1 ; equivalent to 7.32 mg gallic acid per kg per day) or vehicle by gavage. In SHRs, 4-week RWPS supplementation progressively decreased blood pressure, reaching 11.5% reduction at the end of the study ( p < 0.001). RWPS consumption also increased the ferric reducing ability of plasma and attenuated the oxidation of plasma lipids and proteins, as evidenced by F2 -isoprostanes, malondialdehyde and protein carbonyl groups as oxidative stress biomarkers. Moreover, nitric oxide production (indirectly measured) was 1.5-fold higher in SHRs + RWPS than that in SHRs ( p < 0.05). These beneficial effects were partly attributed to the ability of RWPS-derived bioactive compounds to modulate aortic gene expression, with eNOS, SOD2 and HO-1 over-expression, ACE down-regulation, and no changes in NOX4. In conclusion, this study suggests the potential of red wine pomace-derived seasonings to help in the management of hypertension.